Monitoring Social Living Experience in Urban Space with Future Research Approach (Case Study: Zanjan City) - MOHAMAD TAGHI HEYDARI; alireza anbarloo; maryam rahmani; hoseein tahmasebi (نشریه جغرافیا و برنامه‌ریزی, 2020)
Introduction One of the most important issues is the theory of sustainable development and its recent approach (livable) which, like other modern approaches to the theory of sustainable development, while posing a problem in the city, leads us to have a more favorable city for sustainable urban life and development. The origins of the worn-out texture of the central part of Zanjan, which is the core of the city, exhibits a different face than the city, from various aspects of environmental sustainability including environmental, economic and social health. Therefore, the present study focuses on the worn-out texture of the central part of Zanjan by analyzing the livelihood approach to analyze the status of its social viability. Understanding this process will undoubtedly be an important tool in achieving the long-term aspiration of aging tissue planning.    Methodology The present study seeks to explain the present situation and to write a scenario for the future situation. Therefore, the future research approach is dominant in this research. In this respect, the research method is based on heuristic analysis. Field studies (observation, interviews and questionnaires) and library studies (study of documents, statistics and research backgrounds and theories) were used for data collection. The statistical population of the study consisted of worn-out texture of Zanjan. According to population of 75057, wear-resistant texture of Zanjan city, using Cochran sampling method with 0.05 error, the total sample population was 384 persons. Factor analysis, goodness-of-fit analysis and interaction / structural effects analysis were used for data analysis. Results and discussion Investigation of the relationship between independent variables (education, social capital, security, health and leisure) and dependent (factor bias) based on factor loadings (γ) shows that among the five dimensions relationship with biodiversity of Zanjan, social capital component with Standard coefficient 1.09 has the highest and security component with standard coefficient 0.08 has the least relationship with Zanjan city's viability. Therefore, in order to achieve the social indicators of a sustainable city, the social security component in Zanjan needs to be further strengthened. On the other hand, examining the relationship between latent variables (education, social capital, security, health and leisure) and explicit (components shown in a rectangular form) based on factor loadings (λ) shows that among the components of education Per capita index of educational spaces with standard coefficient of 0.34 in social capital component of neighborhood trust index with standard coefficient of 0.34, in health component of public health care quality index with standard coefficient of 0.24, in security component of voluntary security patrols index with standard coefficient of 0.98, in Leisure component of the quality index of access to leisure and sports facilities with the coefficient of standard 0.34 has the most to do with the social viability of Zanjan.   Conclusion In this regard, the results of the research approach with MICMIC showed that indicators of "satisfaction with space for the elderly", "level of social corruption", and "informal night-time surveillance through diversity of uses", and "membership in public institutions" It has the most instability. The result is that in the future, the sustainability of Zanjan city in terms of socio-cultural structures is an improvement of these indicators. On the other hand, considering the socio-cultural structure of the worn-out texture of Zanjan with high levels of social capital, explaining the relationships between the components showed that the indicators of "educational spaces per capita", "drug use", "quality of access to Libraries "," pedestrian and nocturnal security, "" access to private health care, "and" membership of public institutions "have very strong relationships. And these are bilateral relations with the "per capita educational spaces" component. This practice also shows that the issue of education and reaching its standards is one of the most important social priorities for making Zanjan city viable for future generations.